Anatomies of Inequality: Considering the Emotional Cost of Aiming Higher for Marginalised, Mature Mothers Re-Entering Education. Issue 1 (May 2013) - Mannay, Dawn; Morgan, Melanie
The Anatomy of Economic Inequality in Wales (2011) provides quantitative evidence for the pervasive nature of class-based inequalities in education, demonstrating that an individual in social housing is approximately 10 times less likely to be a graduate compared to those in other types of accommodation. This article moves beyond the baseline figures and argues that for marginalised, mature mothers re-entering education, the emotional cost is often one that they are unable to pay, and that practitioners and policy makers need to be aware of, and responsive to their situation so that retention and completion rates can be improved. The article presents case studies from two research projects, which aimed to explore and represent the educational experiences of working-class mature students in urban south Wales. The article focuses on the accounts of women who completed Access courses and gained places in post-1992 universities, focusing on their initial aspirations and later disappointments. The article examines the ways in which classed, gendered and relational positionings conflicted with their education trajectory and often contributed to their withdrawal from academia.